Chansons madécasses. Pieśni Madagaskaru - Parny, Évariste Désiré (University of Warsaw Press, 2025)
The publication is concerned with Évariste Désiré Parny, the author of “The Songs of Madagascar”(1787) as well as the history of Madagascar and other islands in the context of their colonization by the French in the 17th and the 18th century. The reader is presented with three translations of Parny’s Enlightenment work: by Kazimierz Brodziński (1819), a modern philological translation by the Translation Group of Romance Studies Faculty and an outstanding translation by Małgorzata Sokołowicz. The book also contains a Creole translation of several songs.